2021
DOI: 10.1021/acs.inorgchem.0c02996
|View full text |Cite|
|
Sign up to set email alerts
|

Benchmarking Coordination Number Prediction Algorithms on Inorganic Crystal Structures

Abstract: Coordination numbers and geometries form a theoretical framework for understanding and predicting materials properties. Algorithms to determine coordination numbers automatically are increasingly used for machine learning and automatic structural analysis. In this work, we introduce MaterialsCoord, a benchmark suite containing 56 experimentally-derived crystal structures (spanning elements, binaries, and ternary compounds) and their corresponding coordination environments as described in the research literatur… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 73 publications
(163 reference statements)
0
33
0
Order By: Relevance
“…24 The dopant metals were selected based on a combination of probabilistic model, crystal-near-neighbor (CrystalNN), which is implemented in the Pymatgen library, and available literature reports. [25][26][27][28][29] From many candidates in periodic tables, we selectively applied seven different dopant metals (Zn, Al, Bi, Co, Ni, Fe and Cu) that were verified as an efficient medium in LIB cathode materials. 30 To identify the suitable doping level in K x MnO 2 , thereafter, the combined ML and DFT prediction was further performed in the dopants concentration of 0, 0.1 and 0.2.…”
Section: Combined ML and Dft Screeningmentioning
confidence: 99%
“…24 The dopant metals were selected based on a combination of probabilistic model, crystal-near-neighbor (CrystalNN), which is implemented in the Pymatgen library, and available literature reports. [25][26][27][28][29] From many candidates in periodic tables, we selectively applied seven different dopant metals (Zn, Al, Bi, Co, Ni, Fe and Cu) that were verified as an efficient medium in LIB cathode materials. 30 To identify the suitable doping level in K x MnO 2 , thereafter, the combined ML and DFT prediction was further performed in the dopants concentration of 0, 0.1 and 0.2.…”
Section: Combined ML and Dft Screeningmentioning
confidence: 99%
“…To measure domain shift, CMD was computed in the learned feature space of the last frozen convolutional layer of each extractor. We found that CMD computed in this feature space showed a strong positive trend with CMD computed in the space of features procedurally generated from local atomic structure order parameters [50,51], suggesting the learned feature space faithfully distinguishes atomic structures (see Fig. 6).…”
Section: Understanding Positive and Negative Transfermentioning
confidence: 73%
“…Following the recent findings on benchmarking nearest neighbors algorithms by Pan et al ., we consider an atom a neighbor if the solid angle is larger than 50 % of the maximum solid angle, i. e . σ>0.5*σmax ; [38] …”
Section: Resultsmentioning
confidence: 99%